On mitigating emissions leakage under biofuel policies. Issue 2 (25th May 2015) - Rajagopal, Deepak
Abstract: A reason for much pessimism about the environmental benefits of today's biofuels, essentially corn and sugarcane ethanol, is the so‐called indirect land‐use change (ILUC) emissions associated with expanding biofuel production. While there exist several simulation‐based estimates of indirect emissions, the empirical basis underlying key input parameters to such simulations is not beyond doubt, while empirical verification of indirect emissions is hard. Regardless, regulators have adopted global warming intensity ratings for biofuels based on those simulations and in some case are holding regulated firms accountable for (some forms of) leakage. Suffice to say that both the estimates of and the approach to regulating leakage are controversial. The objective of this study is therefore to review a wider economic in order to identify a broader set of policy options for mitigating emissions leakage. We find that controlling leakage by affixing responsibility to regulated firms lacks support in the broader literature, which emphasizes alternative approaches.